MetaboSignal, a network-based approach for topological analysis of metabotype regulation via metabolic and signaling pathways - Rodriguez,Martinez A; Ayala,R; Posma,JM; Neves,AL; Gauguier,D; Nicholson,JK; Dumas,ME (Bioinformatics, 2016)
MetaboSignal is an R package that allows merging metabolic and signaling pathways reported in the Kyoto Encyclopaedia of Genes and Genomes (KEGG). It is a network-based approach designed to navigate through topological relationships between genes (signaling- or metabolic-genes) and metabolites, representing a powerful tool to investigate the genetic landscape of metabolic phenotypes.